Observation of a leatherback sea turtle, Dermochelys coriacea, in the Gulf of Corinth, Greece - Giovanni Bearzi; Paolo Casale; Dimitris Margaritulis; Silvia Bonizzoni; Nina Luisa Santostasi (2015)
Published records of the leatherback sea turtle, Dermochelys coriacea (Vandelli 1761) in the Mediterranean are few, particularly in comparison to those of the loggerhead sea turtle Caretta caretta (Casale & Margaritoulis 2010). However, these records indicate that leatherbacks occur throughout the basin, from the Gibraltar Strait to the easternmost part, and enter the basin at a relatively large size (large juveniles/adults), with no evidence of breeding in the Mediterranean (Casale et al. 2003). The species is classified globally as Vulnerable by the International Union for Conservation of Nature (Wallace et al. 2013). Mediterranean leatherbacks are considered part of the north-Atlantic regional management unit of this species, categorized as Low risk–Low threat (Wallace et al. 2011). Leatherbacks have been reported from the Ionian and the Aegean Seas, including coastal areas. In Greece, all published records have concerned dead animals, usually stranded on beaches (Margaritoulis 1986). Information on the diving behavior of leatherbacks at non-breeding grounds is limited, derived from satellite tracking or animal-borne cameras, and most of the information is from postnesting females (Fossette et al. 2010; Heaslip et al. 2012; Shillinger et al. 2011). Here, we report an encounter with a leatherback in the semi-enclosed Gulf of Corinth, Greece, contributing one of the few detailed observations of a live individual of this species in the entire Mediterranean region.